Legal Protection for Workers in Gorontalo: Towards aCivilized Justice System - Mawardi De La Cruzz; Firmansyah Abdillah; Mohammad Haekal Rahman (Indonesian Civil Law Review, 2025)
This study examines legal protection for workers in Gorontalo Province, focusing on the informal sector that dominates the regional employment structure. Data shows that until August 2024, as many as 61.45% of the workforce works in the informal sector with an average income of IDR 1,608,048 per month, lower than the Gorontalo UMP and the national average. Low access to social security schemes such as BPJS, lack of legal education, and weak labor supervision due to limited personnel and budgets exacerbate the vulnerability of workers, especially women who face wage inequality of up to 23%. Local government efforts such as the PBI program and the protection of non-ASN workers show progress, but they are still far from reaching the entire vulnerable worker population. This research emphasizes the importance of substantive justice-based policy reformulation, by integrating aspects of gender, social protection, and effective law enforcement. The goal is to build a civilized and inclusive labor system, in accordance with the principles of the rule of law that protect the dignity and human rights of every worker.